Anthropomorphology of selected muscles of lower extremity of Hylobates lar - Marecki, Bogusław; Jakubowicz, Marian (Anthropological Review, 1978)
The paper presents characteristics of 16 muscles of lower extremity of a gibbon with respect to their measurements and descriptive traits. Metric characteristics and descriptive traits of these muscles were compared to respecive data on chimpanzess, human fetuses and adults.